MODEL PENYELENGGARAAN STUDIO PEMBELAJARAN PROGRAM TELEVISI YANG IDEAL UNTUK INSTITUSI PENDIDIKAN PERTELEVISIAN - Adji, Titus Soepono; Agung, I Putu Suhada (Institut Seni Indoensia Surakarta, 2017)
The learning studio for television programs was the space used by educational institutions in television program as studio simulations that demonstrate television stations, in organizing the productionof television programs for students. This room was the main infrastructure that should be owned byeducational institutions that run television programs, considering most television programs were produced in the studio. Currently, many educational institutions opened television and broadcastingprograms, but in reality not all television program administrators had studio that met the standards.This caused the learning process did not take place optimally. The number of work produced bystudents each semester were not maximum, the production ability was also not optimum, and thiscaused the expected output from graduates in mastering in-door studio production became not maximum too. The purpose of this research was to arrange the model of organizing studio production fortelevision program in educational institution so that it could increase the target of learning to beachieved. This research was a qualitative research, with data collection methods in the form of observation and interview with purposive sampling model in some educational institutions. The analysisused was qualitative verification analysis. The conclusion was to design an adaptive television studiothat could be held in an existing room while maintaining the standards of television program production.Keywords: Learning studio model,production studio of television program.